Learner discipline: An Australian perspective - Stewart, D. (Koers, 2004)
Australian schools by and large are safe schools. Nonetheless discipline problems do exist – including bullying behaviour. For this kind of problem schools should have management policies in place. As traditional behaviour-management practices – including corporal punishment – are largely prohibited in Australian schools, contemporary practices centre on management through supportive school programmes, including appropriate curricula and school-support structures. This article supports the belief that measures such as the exclusion of misbehaving learners should be treated with caution. Measures such as this might not reflect accepted international principles and practices and should only be exercised in the most extreme circumstances. The article also supports the view that it is part of the school’s role to ensure that all learners are aware of the reality that while they have rights, they also have corresponding responsibilities. This awareness is more likely to be achieved in a supportive school culture where each learner is recognised as having unique qualities that can mature and grow in an appropriate learning environment.